Prediction of lateral lymph node metastasis using OSNA method for mesorectal lymph nodes in low rectal cancer: A prospective study by the Kanagawa Yokohama Colorectal Cancer Study Group (KYCC1801). Issue 3 (27th October 2021) - Numata, Masakatsu; Shiozawa, Manabu; Godai, Teni; Kazama, Keisuke; Okamoto, Hironao; Kato, Aya; Katayama, Yusuke; Sato, Sumito; Sugano, Nobuhiro; Kohmura, Takashi; Higuchi, Akio; Saito, Kentaro; et al.
Abstract: Background and Objectives: Contrary to the Japanese guidelines recommendations regarding lateral lymph node dissection (LatLND) for rectal cancer, its omission is common in clinical practice without reliable omission criteria. Negative pathological mesorectal lymph node metastasis (MesLNM) is reportedly highly correlated with negative pathological lateral lymph node metastasis (p‐LatLNM); however, this cannot be used as a criterion because pathological features are revealed postoperatively. Herein, we prospectively evaluated the negative predictive value (NPV) of MesLNM diagnosed via the one‐step nucleic acid amplification (OSNA) method for p‐LatLNM. Methods: This prospective study was conducted at a single academic study group in Japan. The key eligibility criterion was mid‐to‐low rectal cancer planned to be treated using mesorectal excision with LatLND. According to the study protocol, the OSNA method was considered useful if the point estimate of the NPV exceeded 95%. Results: Preoperative case registration was conducted between 2018 and 2020; 34 patients were registered. Among these, 16 were negative for OSNA‐MesLNM, and negative p‐LatLNM was confirmed in all cases. The point estimate of the NPV was 100%, with the 95% confidence interval ranging from 79.4% to 100.0%. Conclusions: The OSNA method is useful in selecting patients in whom LatLND can be omitted in real‐world clinical practice.